Predictive Value of Psychological Scales for Hospitalization of Elderly Suicide Attempters - Eundo Kim; Ki Young Jeong; Jong Seok Lee; Han Sung Choi (Annals of Geriatric Medicine and Research, 2017)
Background : Suicide lethality and intent are known potential determinants of hospitalization, and high degrees of these factors are discriminating characteristics of elderly suicide attempters. We evaluated their ability to predict hospitalization in elderly suicide attempters. Methods : Via medical charts and interview questionnaires, data were collected retrospectively on suicide attempters aged 65 years and older who presented to the Emergency Department (ED) from January 2012 to December 2016. Subjects were divided into hospitalization and discharge groups. Degrees of suicide lethality and intent were evaluated using the Risk-Rescue Rating Scale (RRRS) and the Suicide Intent Scale (SIS), respectively. The predictive abilities of these scales for hospitalization were assessed using logistic regression analysis and compared with the area under the receiver operating characteristic curve. Results : Of 168 patients, 110 (65%) were hospitalized. The RRRS and SIS scores for hospitalized patients were significantly higher; both scales were identified as independent predictors of hospitalization. The predictive performance of the RRRS for hospitalization was significantly superior to that of the SIS. Among SIS subscales, only the SIS part 2 was found to be an independent predictor of hospitalization. Its performance tended to be higher than the SIS, and comparable to the RRRS. The RRRS and SIS part 2 had greater sensitivity for predicting hospitalization than specificity. Conclusion : For elderly suicide attempters in the ED, the RRRS is a useful predictor of hospitalization. Further investigations based on the feasibility of the SIS part 2 as a predictor are needed.